Ka khyaṅʻ Nhacʻ khraṅʻʺ Kharacʻyānʻ ʼA phvaiʹ khyupʻ, 3/300 sāsanā lupʻ ṅanʻʺ ca ʼupʻ, 1978-1981 - ʼAmʻ dī Kho Choṅʻ, 1944- (Rvhe Pu ra puidʻ Cā pe, 1991)
Evangelistic work by 300 Evangelists for a period of 3 years in Burma; activities of the Ka khyaṅʻ Nhacʻ khraṅʻʺ Kharacʻyānʻ ʼA phvaiʹ khyupʻ (Kachin Baptist Convention), during the period 1978-1981.